Aktualisasi Arbeiter Samariter Bund dalam Bidang Pengurangan Risiko Bencana Inklusif di Provinsi Jawa Tengah - Muhammad Jaffar Rachmaditya; Hermini Susiatiningsih; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
Central Java is one of the provinces that occupies the first position which is said to be a disaster laboratory in Indonesia. However, the Central Java BPBD (Regional Disaster Management Agency) is still lacking in capacity building in the field of inclusive disaster management. Therefore, the Central Java Government cooperates with an INGO, namely ASB (Arbeiter-Samariter-Bund). The reason is that one of ASB's focuses is inclusive disaster risk reduction. Both nationally and internationally, the participation of persons with disabilities is seen as the key in increasing inclusive disaster management capacity. Based on these problems, it is interesting to study the role of ASB in including DRR in order to increase the capacity of the Central Java BPBD and the participation of persons with disabilities. The purpose of this study is to analyze the role of INGOs in capacity building through international collaboration with local governments in the field of inclusive disaster risk reduction. This study uses 3 concepts as an analytical tool, namely International Cooperation, inclusive Disaster Risk Reduction, and Capacity in Disaster Risk Reduction. The author uses qualitative research methods with analytical descriptive type. The results of this study indicate that ASB's role in providing insight creates a positive impact in the field of inclusive disaster risk reduction for both persons with disabilities and related institutions, which changes conditions that were initially vulnerable to capacity.